The Effect of Adding Different Spray Solutions on the Growth of Cypress and Thoya Forest Tree Seedlings - Abdulazeez , Nermen Asad; Rashid , Pinar Najdat; Gedik , Ahmed Abdulsalam Abbas (American Journal of Botany and Bioengineering, 2026)
This study was conducted in the wooden canopy belonging to a farmer within the Kirkuk Irrigation Project during 2025 using one-year-old forest seedlings of cypress and thoya types, and the type of seedlings was adopted as the first factor, while the second factor included four types, namely plain water, magnetized water, foliar manure (Hybox). The co-treatment between magnetized water and foliar manure, while the third factor was represented in spraying periods of 20, 40 and 60 days. The seedlings were planted in sand ponds with dimensions of 1×3 m, with 30 seedlings per basin according to the complete random design, and the measurements lasted from April to November and included the trait of stem length and stem diameter, and then the data were analyzed using SPSS software version 17. The results showed a clear superiority of the magnetized water treatment in all the studied traits, as it recorded the highest average leg length of 43.27 cm and the leg length reached 47.18 cm in November, while it also excelled in the stem diameter trait with an average of 6.89 mm and a final value of 7.57 mm, reflecting its strong positive effect in promoting vegetative growth and increasing stem thickness. The foliar fertilizer treatment gave average results in stem length with an average of 35. 23 cm and reached 40.12 cm at the end of the season, while the stem diameter reached 5.60 mm with a maximum of 6.18 mm. However, the combined treatment between magnetized water and foliar manure also recorded average values as the average leg length reached 35.29 cm and reached 39.08 cm. The average leg diameter was 5.88 mm and a maximum of 6.81 mm, but it did not surpass magnetized water alone. As for the plain water treatment, the lowest values were recorded in both qualities, with an average leg length of 34.46 cm and a maximum of 37.86 cm, while an average leg diameter of 5.82 mm reached 6.31 mm at the end of the season. In general, the best growth performance was in favor of the magnetized water treatment, which excelled in the length and diameter of the stem, followed by the foliar manure treatment and then the co-treatment, while the plain water treatment came with the lowest values. This confirms the importance of using catalytic treatments in improving the growth of cypress and thoya seedlings.